Attachment security representations in institutionalized children and children living with their families: Links to problem behaviour - Torres, Nuno (2012)
The present work analyses differences in the attachment representations of institutionalized children as compared with children from low and high educational level living with their natural families. Participants were 91 Portuguese children, 52% girls, aged 48–96 months. There were three different groups: 19 institutionalized children, 16 low educational level families’ children and 56 from high educational level families’. Attachment representations were assessed for Security of the narratives of the Attachment Story Completion Task (ASCT). Psychopathological symptoms were assessed using the Child Behaviour Checklist for parents and caretakers. Verbal skills were assessed using the Wechsler Preschool and Primary Scale of Intelligence—Revised. Results show that institutionalized children have signifi cantly lower security of attachment representations, less verbal skills and higher aggressive behaviour than the other two groups. Attachment representations were associated with social/withdrawal and aggression, independently of age, verbal skills and parents’ education. The main effect of institutionalization on externalizing aggressive behaviour was completely mediated by the security of attachment representations.